An In Vitro Comparison of Shear Bond Strength of Zirconia to Enamel Using Different Surface Treatments. Issue 2 (26th July 2013) - Zandparsa, Roya; Talua, Nayrouz A.; Finkelman, Matthew D.; Schaus, Scott E.
Abstract Purpose The purpose of this in vitro study was to compare the shear bond strength of an airborne‐particle abraded zirconia, an acid‐etched zirconia (Piranha solution), an Alloy Primer treated zirconia, and a silaned zirconia to enamel, all bonded with a phosphate‐methacrylate resin luting agent. Materials and Methods Seventy extracted intact human molars were collected, cleaned, and mounted in autopolymerizing acrylic resin, with the experimental surface of the teeth exposed. The specimens were randomly divided into seven groups of zirconia specimens (4 mm diameter, 2 mm thick). Group 1: Airborne‐particle abrasion; group 2: Airborne‐particle abrasion and Z‐PRIME Plus; group 3: Airborne‐particle abrasion and alloy primer; group 4: Piranha solution 7:1; group 5: Piranha solution 7:1 and Z‐PRIME Plus; group 6: Piranha solution 7:1 and Alloy primer; group 7: CoJet and silane. All specimens were luted with a phosphate‐methacrylate resin luting agent (Panavia F2.0) and stored in distilled water for 1 day, then thermocycled (5°C and 55°C) for 500 cycles and tested for shear bond strength (SBS), measured in MPa, with a universal testing machine at a 0.55 mm/min crosshead speed. All specimens were inspected under a scanning electron microscope to determine mode of failure. The mean values and standard deviations of all specimens were calculated for each group. A one‐way ANOVA was performed, and multiple pairwise comparisons were then completed with post hoc Tukey test (alpha = 0.05). Results The airborne‐particle abrasion and Z‐PRIME Plus group resulted in a significantly higher SBS than the other groups (21.11 ± 6.32 MPa) (p < 0.001). The CoJet and silane group (15.99 ± 8.92 MPa) and airborne‐particle abrasion and alloy primer group (11.07 ± 4.34 MPa) showed high shear bond strength but not statistically significant from the airborne‐particle abrasion group (14.23 ± 5.68 MPa). Failure mode was predominately mixed in groups 1, 2, 3, and 7 with islands of retained resin on the zirconia and enamel surfaces; however, groups 4, 5, and 6 showed mostly adhesive failures, which left the zirconia surface free of the adhesive materials. No cohesive failures of the substrates (ceramic, resin, or enamel) were observed. Conclusion Airborne‐particle abrasion followed by the application of a zirconia primer produced the highest bond strength to enamel. Therefore, it can be recommended as a promising surface treatment method to achieve a durable bond to densely sintered zirconia ceramics.